БЎЛҒУСИ ЁШ КАДРЛАРНИ ТАЙЁРЛАШДА ЖИСМОНИЙ ТАРБИЯНИНГ РОЛИ - Қанназаров, А.Г. (SCIENCE and SOCIETY, 2023)
This article is intended for the use of informational technologies in the health and well-being of the younger generation.
Keywords: he effectiveness of physical education of students; the system of physical education of young professionals; The current state of health of students; the universal possibilities of physical education and sport; a healthy lifestyle; the role and importance of pedagogical and information technologies in strengthening students' physical culture